A history of modern Iran - Abrahamian, Ervand 1940- ([New York] Cambridge University Press, 2018)
"In a radical reappraisal of Iran's modern history, Ervand Abrahamian traces the country's traumatic journey from the mid-nineteenth century to the present day, through the discovery of oil, imperial interventions, the rule of the Pahlavis, and the birth of the Islamic Republic. The first edition was named the Choice Outstanding Academic Title in 2009. This second edition brings the narrative up to date, with the Green uprisings of 2009, the second Ahmadinejad administration, the election of Rouhani, and the Iran nuclear deal. Ervand Abrahamian, who is one of the most distinguished historians writing on Iran today, is a compassionate expositor, and at the heart of the book is the people of Iran, who have endured and survived a century of war and revolution"--Provided by publisher.
"Iran entered the twentieth century with oxen and wooden plough. It exited with steel mills, one of the world's highest automobile accident rates, and, to the consternation of many, a nuclear program. This book narrates the dramatic transformation that has taken place in twentieth-century Iran. Since the main engine of this transformation has been the central government, the book focuses on the state, on how it was created and expanded, and how its expansion has had profound repercussions not only on the polity and economy, but also on the environment, culture, and, most important of all, wider society. Some repercussions were intended; others, especially protest movements and political revolutions, were not. This book may appear somewhat quaint and even insidious to those convinced that the state is inherently a part of the problem rather than solution of contemporary dilemmas. But since this book is about major transformations, and these transformations in Iran have been initiated invariably by the central government, it will focus on the latter hopefully without falling into the Hegelian-Rankean pitfalls of glorifying the state"--Provided by publisher.
Machine generated contents note: Introduction -- 1. "Royal despots": state and society under the Qajars -- 2. Reform, revolution, and the Great War -- 3. The iron fist of Reza Shah -- 4. The nationalist interregnum -- 5. Muhammad Reza Shah's White Revolution -- 6. The Islamic Republic; Notes -- Bibliography -- Further Reading -- Index.
Includes bibliographical references (pages 226-228) and index.
Keywords: Iran -- History -- 20th century